Control strength lightweight mortar made by recycled concrete aggregate and expanded perlite - Ahmad Syauqi Md Hasan; Noorsuhada Md Nor; Amril Hadri Jamaludin; Amir Khomeiny Ruslan; Nur Masyitah Osman; Sherliza Zaini Sooria; Soffian Noor Mat Saliah; Mohd Azrizal Fauzi (Penerbit Universiti Kebangsaan Malaysia, 2024)
The use of recycled concrete aggregate (RCA) in the production of concrete structures in Malaysia is minimal and does not match the amount of recycled concrete waste produced during a similar period. Moreover, there is a growing need to shorten the construction period, which necessitates the use of lighter concrete materials to produce lighter material with a minimal strength that able to act as part of the structures. Hence, this study aims to analyse the physical and mechanical properties of control strength lightweight mortar (CSLM) made from RCA and expanded perlite (EPA). The nominal size of crushed RCA and EPA was 4.75 mm, like the natural sand (NA) used. Several ratios of RCA, NFA, and EPA (fine aggregate) were employed to determine the optimal ratio of fine aggregate to cement. The CSLM underwent testing for its uniaxial compressive strength at 3, 7, and 28 days, while flexural strength was tested only at 28 days. It is found that the ideal proportion of RCA and EPA in CLSM is 40% and 20% of the total fine aggregate content, respectively. Meanwhile, the optimal mix ratio for CSLM consists of 40% RCA, 40% NFA, and 20% EPA. Hence, it can be concluded that the presence of residual mortar in RCA increased the water absorption rate, resulting in lower compressive and flexural strength when higher proportions of RCA and EPA were used. Studying CLSM using RCA and EPA offers the benefit of creating more sustainable construction materials by reducing waste and conserving natural resources.